Review on the Different Approaches to Paleo-environment and Paleo-climate Research - Van Vuong, Nguyen; Thi Thu Hoai, Luong; Dinh Nguyen, Nguyen; Nguyen Ha Vu, Pham; The Hung, Nguyen; Thi Huong, Vu (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 3DO - 10.25073/2588-1094/vnuees.4255, 2018)
Abstract: This paper aim to review currently four main approaches to paleoenvironment and paleoclimate research including: 1) paleotonlogy, 2) sedimentology, 3) major and trace element geochemistry, 4) stable isotopes. Sedimentary and geochemical proxies are widely used for many different sedimentary environments and ages. Paleontological proxies have limitation due to the poor preservation of fossil. The use of stable isotopes proxy to study paleo-environment and paleoclimate is new trend that can be applied to wide variety of subjects, from organisms to minerals sensitive to environmental change. The environmental and paleoclimate information obtained from the above four approaches is not the same in terms of information type and level of detail. Paleontology only provides general information on the geographical conditions such as the continental environment, shallow seas, deep seas and continental shelves without detail on the environmental characteristics. Sedimentary records are likely to provide more detail on environmental and geographical information than paleontology proxies. The geochemical proxies provide information related to redox, humid or arid condition, high or less precipitation. Stable isotope provides the most quantitative approach compared to the others. The information obtained from this approach is based primarily on oxygen and carbon isotopes to reconstruct the history of temperature changes in the ocean and atmospheric environment. The quantitative level of the information obtained is gradually increased from the palaeontological, sedimentary, geochemical to stable isotope proxy. There is no unique optimal approach to paleo-environmental and paleo-climate research, therefore, in order to get detailed and quantifiable information it is required to apply synchronously all four approaches mentioned above. Keywords: Paleo-environment, paleoclimate, proxy. References [1] Nesbitt, H.W. and G.M. Young, Early Proterozoic climates and plate motions inferred from major element chemistry of lutites. Nature, 1982. 299: 715-717. [2] Zhang, J., T. Fan, T.J. Algeo, Y. Li, and J. Zhang, Paleo-marine environments of the Early Cambrian Yangtze Platform. Palaeogeography, Palaeoclimatology, Palaeoecology, 2016. 443: 66-79. [3] Amekawa, S., K. Kubota, Y. Miyairi, A. Seki, Y. Kawakubo, S. Sakai, P. Ajithprasad, H. Maemoku, T. Osada, and Y. Yokoyama, Fossil otoliths, from the Gulf of Kutch, Western India, as a paleo-archive for the mid- to late-Holocene environment. Quaternary International, 2016. 397: p. 281-288. [4] Wang, X., Z. Li, L. Xing, M. Zhang, Y. Liu, C. Cao, and L. Li, Development of a new method for hydrogen isotope analysis of trace hydrocarbons in natural gas samples. Journal of Natural Gas Geoscience, 2016. 1(6): p. 481-487. [5] Lou, Y.-x., X.-s. Fu, X. Yu, Z.-h. Ye, H.-f. Cui, and Y.-f. Zhang, Stable Isotope Ratio and Elemental Profile Combined with Support Vector Machine for Provenance Discrimination of Oolong Tea (Wuyi-Rock Tea). Vol. 2017. 2017. 1-8. [6] Camin, F., M. Boner, L. Bontempo, C. Fauhl-Hassek, S.D. Kelly, J. Riedl, and A. Rossmann, Stable isotope techniques for verifying the declared geographical origin of food in legal cases. Trends in Food Science & Technology, 2017. 61: p. 176-187. [7] Hamre, S.S. and V. Daux, Stable oxygen isotope evidence for mobility in medieval and post-medieval Trondheim, Norway. Journal of Archaeological Science: Reports, 2016. 8: p. 416-425. [8] Zeng, Y., Z. Lai, W. Yang, and H. Li, Stable isotopes reveal food web reliance on different carbon sources in a subtropical watershed in South China. Limnologica, 2018. 69: p. 39-45. [9] Egbobawaye, E.I., Isotopes (13C and 18O) geochemistry of Loower Triassic Montney formation, Northeastern British Columbia. western Canada. Nature Science, 2017. 9(10): p. 355-376. Contreras, D.A., A. Bondeau, J. Guiot, A. Kirman, E. Hiriart, L. Bernard, R. Suarez, and M. Fader, From paleoclimate variables to prehistoric agriculture: Using a process-based agro-ecosystem model to simulate the impacts of Holocene climate change on potential agricultural productivity in Provence, France. Quaternary International, 2018. Li, Y., Y. Liu, W. Ye, L. Xu, G. Zhu, X. Zhang, and C. Zhang, A new assessment of modern climate change, China—An approach based on paleo-climate. Earth-Science Reviews, 2018. 177: p. 458-477. Anderson, T.R., E. Hawkins, and P.D. Jones, CO2, the greenhouse effect and global warming: from the pioneering work of Arrhenius and Callendar to today's Earth System Models. Endeavour, 2016. 40(3): p. 178-187. Gonez, P., H. Nguyên Huu, P. Ta Hoa, G. Clément, and P. Janvier, The oldest flora of the South China Block, and the stratigraphic bearings of the plant remains from the Ngoc Vung Series, northern Vietnam. Journal of Asian Earth Sciences, 2012. 43(1): p. 51-63. Thanh, T.-D. and P. Janvier, Early Devonian fishes from trang Xa (Bac Thai, Vietnam), with remarks on the distribution of the vertebrates in the Song Cau Group. Journal of Southeast Asian Earth Sciences, 1994. 10(3): p. 235-243. Janvier, P., P. Racheboeuf, H. Nguyen Huu, and T. Doan Nhat, Devonian fish (Placodermi, Antiarcha) from Tra Ban Island (Bai Tu Long Bay, Quang Ninh Province, Vietnam) and the question of the age of the Dô Son Formation. Journal of Asian Earth Sciences, 2003. 21(7): p. 795-801. Janvier, P., T.D. Thanh, and P. Gerrienne, Les Placodermes, Arthropodes et Lycophytes des grès dévoniensde Do Son (Hai Phong, Viet Nam). Geobios, 1989. 22(5): p. 625-639. Chernykh, V.V., Paradoxes of stratigraphy. Russian Geology and Geophysics, 2015. 56(4): 532-540. Ogg, J.G., Integrated global stratigraphy and geologic timescales, with some future directions for stratigraphy in China. Earth-Science Reviews, 2018. Pigati, J.S., I.M. Miller, K.R. Johnson, J.S. Honke, P.E. Carrara, D.R. Muhs, G. Skipp, and B. Bryant, Geologic setting and stratigraphy of the Ziegler Reservoir fossil site, Snowmass Village, Colorado. Quaternary Research, 2014. 82(3): 477-489. Botquelen, A., A. Loi, R. Gourvennec, F. Leone, and M.-P. Dabard, Formation et signification paléo-environnementale des concentrations coquillières : exemples de l'Ordovicien de Sardaigne et du Dévonien du Massif armoricain. Comptes Rendus Palevol, 2004. 3(5): p. 353-360. Armynot du Châtelet, É., J.-P. Debenay, D. Degré, and P.-G. Sauriau, Utilisation des foraminifères benthiques comme indicateurs de paléo-niveaux marins ? Étude du cas de l’anse de l’Aiguillon. Comptes Rendus Palevol, 2005. 4(1): p. 209-223. Gayet, M., T. Sempre, H. Cappetta, E. Jaillard, and A. Lévy, La présence de fossiles marins dans le Crétacé terminal des Andes centrales et ses conséquences paléogéographiques. Palaeogeography, Palaeoclimatology, Palaeoecology, 1993. 102(3): p. 283-319. Wickens, G.E., Quaternary plant fossils from the Jebel Marra volcanic complex and their palaeoclimatic interpretation. Palaeogeography, Palaeoclimatology, Palaeoecology, 1975. 17(2): 109-122. Moutinho, L.P., S. Nascimento, A.K. Scomazzon, and V.B. Lemos, Trilobites, scolecodonts and fish remains occurrence and the depositional paleoenvironment of the upper Monte Alegre and lower Itaituba formations, Lower – Middle Pennsylvanian of the Amazonas Basin, Brazil. Journal of South American Earth Sciences, 2016. 72: p. 76-94. Vũ Khúc, Địa tầng các trầm tích Jura biển ở Nam Việt Nam dưới ánh sáng các tài liệu mới (Stratigraphy of Jurassic sediments in South Việt Nam in the light of new data). . TC Khoa học Trái đất, 1993. 15/2: p. 56-64. Olóriz, F., M. Reolid, and F.J. Rodríguez-Tovar, Taphonomy of fossil macro-invertebrate assemblages as a tool for ecostratigraphic interpretation in Upper Jurassic shelf deposits (Prebetic Zone, southern Spain). Geobios, 2008. 41(1): p. 31-42. Sergeev, V.N., The distribution of microfossil assemblages in Proterozoic rocks. Precambrian Research, 2009. 173(1): p. 212-222. Rubinstein, C.V., M. Vecoli, and R.A. Astini, Biostratigraphy and paleoenvironmental characterization of the Middle Ordovician from the Sierras Subandinas (NW Argentina) based on organic-walled microfossils and sequence stratigraphy. Journal of South American Earth Sciences, 2011. 31(1): p. 124-138. Cúc, N.T.T., Địa tầng và môi trường trầm tích Holocen vùng ven biển sông Tiền, LA TS. Địa chất. 2014, Trường Đại học khoa học Tự nhiên. 241. Schwarzacher, W., ed. Chapter 12 Cyclostratigraphy and Milankovitch Cycles In Cyclostratigraphy and the Milankovitch Theory. Developments in Sedimentology, ed. W. Schwarzacher. Vol. 52. 1993, Elsevier. 197-207. [31] Lobo, F.J. and D. Ridente, Stratigraphic architecture and spatio-temporal variability of high-frequency (Milankovitch) depositional cycles on modern continental margins: An overview. Marine Geology, 2014. 352: p. 215-247. Fang, Q., H. Wu, L.A. Hinnov, W. Tian, X. Wang, T. Yang, H. Li, and S. Zhang, Abiotic and biotic responses to Milankovitch-forced megamonsoon and glacial cycles recorded in South China at the end of the Late Paleozoic Ice Age. Global and Planetary Change, 2018. 163: 97-108. Mingxiang, M. and M.E. Tucker, Milankovitch-driven cycles in the Precambrian of China: The Wumishan Formation. Journal of Palaeogeography, 2013. 2(4): p. 369-389. El-Yamani, M., M.S. Mahmoud, K. Al-Ramadan, A. Munnecke, D. Cantrell, W. Abdulghani, and L. Reuß, Microfacies, depositional environments and meter-scale cycles of the middle Jurassic Tuwaiq Mountain Formation, Central Saudi Arabia. Journal of African Earth Sciences, 2018. Truong, M.H., V.L. Nguyen, T.K.O. Ta, and J. Takemura, Changes in late Pleistocene–Holocene sedimentary facies of the Mekong River Delta and the influence of sedimentary environment on geotechnical engineering properties. Engineering Geology, 2011. 122(3): p. 146-159. Nghi, T., M.T. Tân, D.Đ. Lâm, Đ.X. Thành, and H.V. Thức, iến hoá trầm tích và cổ địa lý giai đoạn Pliocen - Đệ tứ lãnh thổ và lãnh hải Việt Nam. . Tạp chí Địa chất, loạt A, phụ trương. , 2000. Nghi, T., N. Biểu, and B.C. Quế, Quy luật phân bố sa khoáng biển trong trầm tích Đệ tứ ở Việt Nam. Địa chất, 1996. 237 p. 19 - 24. Lu, F., X. Tan, T. Ma, L. Li, A. Zhao, C. Su, J. Wu, and H. Hong, The sedimentary facies characteristics and lithofacies palaeogeography during Middle-Late Cambrian, Sichuan Basin and adjacent area. Petroleum, 2017. 3(2): p. 212-231. Balsinha, M., C. Fernandes, A. Oliveira, A. Rodrigues, and R. Taborda, Sediment transport patterns on the Estremadura Spur continental shelf: Insights from grain-size trend analysis. Journal of Sea Research, 2014. 93: p. 28-32. Nghi, T., Địa chất trầm tích Việt nam. 2017: Nxb Đại học Quốc gia Hà Nội. 509. Tu, L., X. Zhou, W. Cheng, X. Liu, W. Yang, and Y. Wang, Holocene East Asian winter monsoon changes reconstructed by sensitive grain size of sediments from Chinese coastal seas: A review. Quaternary International, 2017. 440: p. 82-90. Purkait, B. and D.D. Majumdar, Distinguishing different sedimentary facies in a deltaic system. Sedimentary Geology, 2014. 308: p. 53-62. Liu, X., Y. Sun, J. Vandenberghe, Y. Li, and Z. An, Palaeoenvironmental implication of grain-size compositions of terrace deposits on the western Chinese Loess Plateau. Aeolian Research, 2018. 32: p. 202-209. Harris, P.T., Ripple cross-laminated sediments on the East Antarctic Shelf: evidence for episodic bottom water production during the Holocene? Marine Geology, 2000. 170(3): p. 317-330. Yagishita, K., Planar cross-bedding associated with rip currents of Upper Cretaceous formations, northeast Japan. Sedimentary Geology, 1994. 93(3): p. 155-163. Yagishita, K., Paleocurrent and fabric analyses of fluvial conglomerates of the Paleogene Noda Group, northeast Japan. Sedimentary Geology, 1997. 109(1): p. 53-71. Sun, Q., C. Colin, Z. Liu, S. Mischke, S. Duchamp-Alphonse, C. Zhang, and F. Chen, Climate changes of the northeastern Tibetan Plateau since the late glaciation inferred from clay mineralogy of sediments in Kuhai Lake. Quaternary International, 2017. 440: p. 24-34. Biểu, N., Những kết quả mới trong điều tra địa chất và khoáng sản biển nông ven bờ và thành tạo Pliocen-Đệ tứ thềm lục địa Việt nam. Địa chất và Khoáng sản. Viện NCĐC-KS, 2005. 9: p. 52-64. Li, Y., Y. Lin, and L. Wang, Distribution of heavy metals in seafloor sediments on the East China Sea inner shelf: Seasonal variations and typhoon impact. Marine Pollution Bulletin, 2018. 129(2): p. 534-544. Embry, A.F. and E.P. Johannessen, Chapter Three - Two Approaches to Sequence Stratigraphy, in Stratigraphy & Timescales, M. Montenari, Editor. 2017, Academic Press. p. 85-118. Harnois, L., The C.I.W. index: a new chemical index of weathering. Sedimentary Geology, 1988. 55: p. 319–322. Fedo, C.M., H.W. Nesbitt, and G.M. Young, Unraveling the effect of potassium metasomatism in sedimentary rocks and paleosols, with implications for paleoweathering conditions and provenance. Geology 1995. 23 p. 921–924. Buggle, B., B. Glaser, U. Hambach, N. Gerasimenko, and S. Markovic, An evaluation of geochemical weather indices in loess-paleosol studies. . Quaternary International 2011. 240, : p. 12-21. Sheldon, N.D., Gregory J. Retallack, and Satoshi Tanaka, Geochemical Climofunctions from North American Soils and Application to Paleosols across the Eocene‐Oligocene Boundary in Oregon. The Journal of Geology, 2002. 110(6): p. 687-696. Keul, N., G. Langer, S. Thoms, L.J. de Nooijer, G.-J. Reichart, and J. Bijma, Exploring foraminiferal Sr/Ca as a new carbonate system proxy. Geochimica et Cosmochimica Acta, 2017. 202: p. 374-386. Gussone, N., H.L. Filipsson, and H. Kuhnert, Mg/Ca, Sr/Ca and Ca isotope ratios in benthonic foraminifers related to test structure, mineralogy and environmental controls. Geochimica et Cosmochimica Acta, 2016. 173: p. 142-159. Rashid, S.A. and J.A. Ganai, Depositional environments, provenance and paleoclimatic implications of Ordovician siliciclastic rocks of the Thango Formation, Spiti Valley, Tethys Himalaya, northern India. Journal of Asian Earth Sciences, 2018. 157: p. 371-386. Kaifeng, Y., F. Lehmkuhl, B. Diekman, V. Nottebaum, and G. Stauch, Major and trace elements documented paleoenvironmental and provenance signatures as inferred from the lacustrine sequence of Orog Nuur, southern Mongolia. Geophysical Research Abstracts, 2016. Vol. 18, (EGU2016-1896): p. 1896. Wang, S., D. Dong, Y. Wang, X. Li, J. Huang, and Q. Guan, Sedimentary geochemical proxies for paleoenvironment interpretation of organic-rich shale: A case study of the Lower Silurian Longmaxi Formation, Southern Sichuan Basin, China. Journal of Natural Gas Science and Engineering, 2016. 28: p. 691-699. Xu, F., B. Hu, Y. Dou, X. Liu, S. Wan, Z. Xu, X. Tian, Z. Liu, X. Yin, and A. Li, Sediment provenance and paleoenvironmental changes in the northwestern shelf mud area of the South China Sea since the mid-Holocene. Continental Shelf Research, 2017. 144: p. 21-30. Li, J., S. Tang, S. Zhang, Z. Xi, N. Yang, G. Yang, L. Li, and Y. Li, Paleo-environmental conditions of the Early Cambrian Niutitang Formation in the Fenggang area, the southwestern margin of the Yangtze Platform, southern China: Evidence from major elements, trace elements and other proxies. Journal of Asian Earth Sciences, 2018. 159: p. 81-97. Delpomdor, F., C. Blanpied, A. Virgone, and A. Préat, Paleoenvironments in Meso–Neoproterozoic carbonates of the Mbuji-Mayi Supergroup (Democratic Republic of Congo) – Microfacies analysis combined with C–O–Sr isotopes, major-trace elements and REE+Y distributions. Journal of African Earth Sciences, 2013. 88: p. 72-100. Thanh, T.D., V. Khúc, Đ.T. Huyên, Đ.N. Trưởng, Đ. Bạt, N.Đ. Dỹ, N.H. Hùng, P.H. Thông, P.K. Ngân, T.H. Phương, T.H. Dần, T.T. Thắng, T.V. Trị, and T.V. Long, Các phân vị địa tầng Việt Nam. 2005: Nxb Đại học Quốc gia Hà Nội. 504. Trị, T.V., ed. Địa chất và tài nguyên Việt Nam 1st ed. 2009, Nxb Khoa học và Công nghệ. 645. Yến, C.Đ.H., N.T.T. Hiền, and N.T. Thắm, Sử dụng các thông số trong phân tích foraminifera để đánh giá sự thay đổi của tổ hợp hóa thạch và xác định môi trường giếng khoan bể Nam Côn Sơn. Tạp chí dầu khí số 2007. 4. Hanebuth, T.J.J., U. Proske, Y. Saito, V.L. Nguyen, and T.K.O. Ta, Early growth stage of a large delta — Transformation from estuarine-platform to deltaic-progradational conditions (the northeastern Mekong River Delta, Vietnam). Sedimentary Geology, 2012. 261-262: p. 108-119. Lap, N.V., T.T.K. Oanh, and T. Masaaki, Late Holocene depositional environments and coastal evolution of the Mekong River Delta, Southern Vietnam. Journal of Asian Earth Sciences, 2000. 18(4): p. 427-439. Ta, T.K.O., V.L. Nguyen, M. Tateishi, I. Kobayashi, Y. Saito, and T. Nakamura, Sediment facies and Late Holocene progradation of the Mekong River Delta in Bentre Province, southern Vietnam: an example of evolution from a tide-dominated to a tide- and wave-dominated delta. Sedimentary Geology, 2002. 152(3): p. 313-325. Trang, N.T.H., T. Nghi, and Đ.X. Thành, Đặc điểm tướng trầm tích Pleistocen muộn - Holocen đới bờ châu thổ sông Mê Công. Tạp chí Khoa học ĐHQGHN: Các Khoa học Trái đất và Môi trường, 2016. Tập 32(2S): p. 69-80. Lâm, D.Đ., Tiến hóa Trầm tích Holocen châu thổ Sông Hồng. Tạp chí địa chất, , 2005. Số A288. Tanabe, S., Y. Saito, Q. Lan Vu, T.J.J. Hanebuth, Q. Lan Ngo, and A. Kitamura, Holocene evolution of the Song Hong (Red River) delta system, northern Vietnam. Sedimentary Geology, 2006. 187(1): p. 29-61. Funabiki, A., S. Haruyama, N.V. Quy, P.V. Hai, and D.H. Thai, Holocene delta plain development in the Song Hong (Red River) delta, Vietnam. Journal of Asian Earth Sciences, 2007. 30(3): p. 518-529. Tanabe, S., K. Hori, Y. Saito, S. Haruyama, L.Q. Doanh, Y. Sato, and S. Hiraide, Sedimentary facies and radiocarbon dates of the Nam Dinh-1 core from the Song Hong (Red River) delta, Vietnam. Journal of Asian Earth Sciences, 2003. 21(5): p. 503-513. Li, Z., Y. Saito, M. Eiji, Y. Wang, T. Susumu, and L.V. Quang, Climate change and human impact on the Song Hong (Red River) Delta, Vietnam, during the Holocene. Quaternary International, 2006. 144(1): p. 4-28. Hori, K., S. Tanabe, Y. Saito, S. Haruyama, V. Nguyen, and A. Kitamura, Delta initiation and Holocene sea-level change: example from the Song Hong (Red River) delta, Vietnam. Sedimentary Geology, 2004. 164(3): p. 237-249. Tanabe, S., K. Hori, Y. Saito, S. Haruyama, V.P. Vu, and A. Kitamura, Song Hong (Red River) delta evolution related to millennium-scale Holocene sea-level changes. Quaternary Science Reviews, 2003. 22(21): p. 2345-2361. Nghi, T., Đ.X. Thành, N.Đ. Nguyên, and Đ.M. Tiến, Địa chất Pliocen-Đệ tứ vùng biển Việt Nam và kế cận. 2015: Nxb Đại học Quốc gia Hà Nội. 506. Dương, N.T. and Đ.V. Thuận, Ý nghĩa của phương pháp phân tích bào tử, phấn hoa trong nghiên cứu môi trường trầm tích Holocen vùng đồng bằng Sông Hồng. Tạp chí Khoa học ĐHQGHN: Các Khoa học Trái đất và Môi trường, 2016. 32(2S): p. 249-257. Dương, N.T. and N.M. Linh, Kết quả phân tích bào tử phấn hoa trong hai lỗ khoan vùng Hà Nội và mối liên hệ với biến đổi khí hậu và hệ thực vật trong Holocene. Tạp chí Các Khoa học về Trái đất, 2011. 33(3): p. 297-305. Tue, N.T., P.T. Nguyen, D.M. Quan, L.V. Dung, T.D. Quy, M.T. Nhuan, and N.D. Thai, Sedimentary composition and organic carbon sources in mangrove forests along the coast of northeast Vietnam. Regional Studies in Marine Science, 2018. 17: p. 87-94. Tue, N.T., N.T. Ngoc, T.D. Quy, H. Hamaoka, M.T. Nhuan, and K. Omori, A cross-system analysis of sedimentary organic carbon in the mangrove ecosystems of Xuan Thuy National Park, Vietnam. Journal of Sea Research, 2012. 67(1): p. 69-76.